Molecular cobalt salophen catalyst-integrated BiVO4 as stable and robust photoanodes for photoelectrochemical water splitting - Liu, Yidan; Jiang, Yi; Li, Fei; Yu, Fengshou; Jiang, Wenchao; Xia, Lixin (Journal of materials chemistry. A, Materials for energy and sustainability, 2018)
Photoelectrochemical (PEC) water splitting is a promising method for the conversion and storage of solar energy. A combination of catalysts with photoelectrodes is generally required for the development of active photoanodes in PEC devices. In this work, we present two BiVO4 photoanodes modified with cobalt salophen (Co(salophen)) complexes for PEC water oxidation. The resulting photoanodes show significantly enhanced PEC performance. Under simulated sunlight illumination (AM 1.5G, 100 mW cm−2), high photocurrents of 3.89 mA cm−2 and 4.27 mA cm−2 were obtained for Co1/BiVO4 and Co2/BiVO4, respectively at 1.23 V (vs. the reversible hydrogen electrode (RHE)) in a neutral solution, an almost three-fold enhancement over that of the unmodified BiVO4. Intensity-modulated photocurrent spectroscopy (IMPS) analysis shows that the Co(salophen) complexes not only accelerate the water oxidation reaction but also reduce the surface recombination. The half-cell solar energy conversion efficiencies for Co1/BiVO4 and Co2/BiVO4 were 1.09% and 1.18% at 0.7 V, respectively. Due to their hydrophobic nature, the Co(salophen) complexes can bind strongly to the surface of BiVO4. When the Co2 complex featuring four hydrophobic tert-butyl groups in a salophen ligand was anchored to BiVO4, an extremely stable photocurrent of more than 3.5 mA cm−2 at 1.23 V vs. RHE is sustained for at least 3 h without decay. Such a stable and robust photoanode based on a molecular WOC surpasses those attained by most of the state-of-the-art heterogeneous catalysts.